2021
DOI: 10.1126/scisignal.aba0717
|View full text |Cite
|
Sign up to set email alerts
|

The costimulatory activity of Tim-3 requires Akt and MAPK signaling and its recruitment to the immune synapse

Abstract: Expression of the transmembrane protein Tim-3 is increased on dysregulated T cells undergoing chronic activation, including during chronic infection and in solid tumors. Thus, Tim-3 is generally thought of as an inhibitory protein. We and others previously reported that under some circumstances, Tim-3 exerts paradoxical costimulatory activity in T cells (and other cells), including enhancement of the phosphorylation of ribosomal S6 protein. Here, we examined the upstream signaling pathways that control Tim-3–m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…TIM-3 was initially identified as a molecule expressed by dysregulated, chronically-activated T cells and is generally considered to be a T-cell inhibitory protein (48,49). However, the recent studies have indicated that TIM-3 exerts paradoxical costimulatory effect on T cells, including enhancement of the phosphorylation of ribosomal S6 protein, which is present downstream of T-cell receptor signaling (50,51). We did not investigate the co-stimulatory function of TIM-3 on PB-CAR-T cells; however, based on the in vitro and in vivo potency of TIM-3 positive RA + CAR-T cells, the high expression of TIM-3 and LAG-3 on PB-CAR-T cell surface might not induce exhaustion which could impair the function of PB-CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…TIM-3 was initially identified as a molecule expressed by dysregulated, chronically-activated T cells and is generally considered to be a T-cell inhibitory protein (48,49). However, the recent studies have indicated that TIM-3 exerts paradoxical costimulatory effect on T cells, including enhancement of the phosphorylation of ribosomal S6 protein, which is present downstream of T-cell receptor signaling (50,51). We did not investigate the co-stimulatory function of TIM-3 on PB-CAR-T cells; however, based on the in vitro and in vivo potency of TIM-3 positive RA + CAR-T cells, the high expression of TIM-3 and LAG-3 on PB-CAR-T cell surface might not induce exhaustion which could impair the function of PB-CAR-T cells.…”
Section: Discussionmentioning
confidence: 99%
“…MHC molecules acquired by trogocytosed antigen-specific T cells are cointernalized with TCRs through endocytosis and localized in endosomes and lysosomes. Our findings show that Tim-3, which is recruited to the immunological synapse upon T cell activation (39,40), plays a critical role in driving pMHC and membrane-associated protein transfer from Tim-3 + APCs to PS + activated T cells both in vitro and in melanoma-bearing mice, regulating T cell trogocytosis and fratricide killing.…”
Section: Discussionmentioning
confidence: 80%
“…Three subfamilies were found in the MAPK signaling pathway, including the extracellular-signal-regulated kinases (ERK MAPK, Ras/Raf1/MEK/ERK), the c-Jun N-terminal or stress-activated protein kinases (JNK, SAPK), and p38 [ 16 18 ]. Once the pathway was activated, a number of downstream target kinases including MAPKAPK3 could be activated [ 19 ]. Recently, some researchers have fabricated an in situ injectable hydrogel which can markedly accelerate diabetic wound healing through activating the TGF- β /MEK/MAPK signaling pathway [ 20 ].…”
Section: Discussionmentioning
confidence: 99%